2019
DOI: 10.1111/emre.12341
|View full text |Cite
|
Sign up to set email alerts
|

Do Distinct CSR Categories have Distinct Determinants? The Roles of Market Structure and Firm Size

Abstract: Despite the existing vast literature on corporate social responsibility (CSR), there is a lack of research on the determinants of CSR categoriesenvironment, employees, community, and governance. Why do some firms dedicate more effort to community, while others focus on environment or employees? We address these issues with special attention to the roles of market structure and firm size, controlling for industry, geography, regulatory and macroeconomic variables. Answers are relevant for firms' strategic decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…In regard to the control variables, there were positive influences of the company size (CS), concentration of ownership (COO), and internationalization (INT) on the CSR performance of the companies investigated. Regarding size, larger companies exhibit better CSR performance, thus corroborating several studies on the determinants of CSR (Reverte, 2009;Gamerschlag et al, 2011;Wang, Song, & Yao, 2013;Kühn et al (2018); Pradhan & Nibedita, 2019;Acabado et al, 2019).…”
Section: Economic Sector (Sector)supporting
confidence: 83%
See 1 more Smart Citation
“…In regard to the control variables, there were positive influences of the company size (CS), concentration of ownership (COO), and internationalization (INT) on the CSR performance of the companies investigated. Regarding size, larger companies exhibit better CSR performance, thus corroborating several studies on the determinants of CSR (Reverte, 2009;Gamerschlag et al, 2011;Wang, Song, & Yao, 2013;Kühn et al (2018); Pradhan & Nibedita, 2019;Acabado et al, 2019).…”
Section: Economic Sector (Sector)supporting
confidence: 83%
“…The results also indicate that companies from the financial sector have better CSR performance, which corroborates the findings of Kühn et al (2018), Gamerschlag et al (2011), andAcabado et al (2019). This behavior may be related to the lower environmental impact of this business sector on society when compared to other economic sectors (Kühn et al, 2018;Acabado et al, 2019).…”
Section: Economic Sector (Sector)supporting
confidence: 82%
“…These findings are in line with those of Youn et al (2015), Udayasankar (2008); Galbreath and Benjamin (2010); and Çera (2020) who concluded that firm size does not matter in CSR. Although they contradict with Acabado et al (2020); Godos-Díez et al (2020); and Orazalin (2019) who argued that firm size is an important determinant of its CSR engagement.…”
Section: Resultsmentioning
confidence: 70%
“…Firm size is measured by taking the natural log of total assets; one of the most frequently used measures for firm size (Salhi et al , 2019; Kachouri et al , 2020; Chakroun et al , 2019). As larger firms possess more resources, they are thus more likely to invest in CSR (Acabado et al , 2020; Godos-Díez et al , 2020). Moreover, because they receive more attention from the public they are under higher pressure to disclose more information about CSR activities to legitimize their activities (Gavana et al , 2017; El-Bassiouny and Letmathe, 2018; Welbeck, 2017; Orazalin, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This study used the CSR ratings of the firms presented in the CSRHub (https://www.csrhub.com), which was a company that specialized in categorizing and reporting the CSR values. The recent CSR‐related studies have used the CSRHub index (Acabado et al, ; Bu, Liu, Wagner, & Yu, ; Thanetsunthorn, ). Furthermore, the CSRHub derived data from various sources for estimating the CSR performance of the firms.…”
Section: Sample and Methodologymentioning
confidence: 99%